Waqf, its substitution (istibdal), and selected resolutions of Islamic Fiqh Academy India : a maqasid al-shari'ah perspective - Ali, Mohammed Farid; U Tun Aung, Maulana Akbar Shah; Gamon, Alizaman Dumangcag (IIUM Press, International Islamic University Malaysia, 2018)
Waqf is a charity in which corpus is maintained and the usufruct is given to the benefisiaries. The continuity of the usufruct depends on the maintenance and management of the corpus. One of the modes used both in classical and modern times to mantain waqf-properties is substitution of one waqf-property with another known as istibdal. This paper reads into istibdal, selected resolutions of Fiqh Academy India and scrutinizes them under the shari'ah objectives of waqf and tabaeeu at ( donation ). The finding shows that modes of istibdal permitted by Islamic law realize the shari'ah objectives of waqf concomitantly. Modes which were not permitted oppose the objectives of the shari'ah. This work is a potential guide for institutions and committees involved with the development of waqf-properties using innovative financing modes.